Performance Analysis of Multiple Virtualized Servers - Sajad Homayoun; Ahmad Jalili; Manijeh Keshtgari (Universitas Sriwijaya, 2015)
Server virtualization is considered as one of the most significant changes in IT operations in the past decade, making it possible to manage groups of servers with a greater degree of reliability at a lower cost. It is driven by the goal of reducing the total number of physical servers in an organization by consolidating multiple applications on shared servers. In this paper we construct several x86_64 servers based on VMware vSphere, and then analyze their performances using open source analyzing tools Pylot and Curl-loader. The results show that despite the enormous potential benefits of virtualization techniques, the efficiency decreased by increasing the number of virtual machines. So, a trade-off is needed between number of virtual machines and expected efficiency of servers.